2004
DOI: 10.1002/hed.20010
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of a randomized controlled trial to evaluate the effects of progressive resistance exercise training on shoulder dysfunction caused by spinal accessory neurapraxia/neurectomy in head and neck cancer survivors

Abstract: The study results demonstrate a high rate of completion and adherence with our PRET program among patients with head and neck cancer. The preliminary findings, although limited, also suggest a potential therapeutic role for resistance exercise as an adjunct to standard physical therapy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(157 citation statements)
references
References 41 publications
4
152
0
1
Order By: Relevance
“…The majority (22 studies) had an intervention group and a control group, in which no physical activity or other treatment was prescribed. Four studies provided an intervention for the comparison group (25,30,35,42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (22 studies) had an intervention group and a control group, in which no physical activity or other treatment was prescribed. Four studies provided an intervention for the comparison group (25,30,35,42).…”
Section: Resultsmentioning
confidence: 99%
“…In the 14 studies that commented on adverse events, 12 indicated that no harm was observed as a result of physical activity during or after cancer treatment. McNeely et al (35) reported that one participant who was nearing the completion of radiation therapy complained of nausea during one activity session, with no further difficulties in participation. Courneya et al (23) reported similar overall rates of adverse events between groups of breast cancer survivors, but the rate of lymphedema in the physical activity group was borderline significantly higher.…”
Section: Resultsmentioning
confidence: 99%
“…22,[42][43][44][45][46] One study examining the effects of resistance exercise in preventing skeletal muscle atrophy of bone marrow transplant recipients receiving total parenteral nutrition found that exercise induced a muscle protein-sparing effect. 22 Study results may have been confounded by variations in baseline arm muscle area and nutrition protocols.…”
Section: Resistance Exercisementioning
confidence: 99%
“…A Cochrane review of randomized trials of very low risk of bias on exercise interventions for shoulder dysfunction in patients with head and neck cancer reported that the pooled data of included trails demonstrated that progressive resisted training improves shoulder pain, shoulder disability and active range of motion in comparison with standard care [53,54].…”
Section: Evidences Of Association Between Physical Activity Exercisementioning
confidence: 99%